Social control in times of increasing neoliberalism in the period of 2020-2023 - Alves, Marilene de Figueiredo; Andrade, Janice Gusmão Ferreira de (Seven Editora, 2023)
The present work aims to analyze social control in a context of resurgence of neoliberalism during the period from 2020 to 2023. Neoliberalism, characterized by policies of economic liberalization, privatization, and reduction of state intervention, significantly impacts the dynamics of citizen participation and supervision of public policies. During this period, an intensification of neoliberal policies has been observed in many countries, which raises questions about how this approach has affected civil society's ability to influence political decisions and protect the public interest. The study explores the implications of neoliberalism for social control, including the decrease in public investment in areas such as health and education, which increases the dependence on civil society in complementing these services and in the search for transparency and accountability. The literature review method used consisted of a systematic analysis of academic studies and government reports that address neoliberalism, social control, and their interactions. Historical, political, and social aspects were considered for a holistic understanding of the dynamics in question. The results highlight the influence of neoliberalism in reconfiguring citizen participation, reflected in the reduction of the State's regulatory role and the growing dependence on civil society to fill gaps in public services. The resurgence of neoliberalism was also associated with economic inequality and the weakening of control institutions. DOI:https://doi.org/10.56238/sevened2023.006-001